Selective catalytic reduction of nitrogen oxide by ammonia over Cu/SAPO-11: a theoretical study - Griffe, Beulah (2020)
Quantum chemistry calculations were carried out using the ONIOM2 methodology at two diferent levels of calculation,B3LYP for the high level and UFF for the low level. These calculations were performed on Cu/SAPO-11, NO–Cu/SAPO-11,NH3–Cu/SAPO-11 and NO+NH3–Cu/SAPO-11 to investigate the reaction pathway of the selective catalytic reduction of nitrogen oxides by ammonia in the presence of Cu/SAPO-11. NH2NO is formed, and then is decomposed into N2 and H2O over Cu/SAPO-11 for the catalytic reduction of NO in two steps. The adsorption energy ΔEads of NO, NH3 on Cu/SAPO-11 and the change of energy of the reduction reaction are presented. The energy profle of the formation of NH2NO–Cu/ SAPO-H key intermediate is shown. Some relevant charges and bond indexes were calculated. On adsorbing NH3 or NO on Cu/SAPO-11 there is charge transfer to the aggregates. Vibrational frequencies of adsorbed NH3, NO and of NH2NO– Cu/SAPO-11cluster are reported. The importance of adsorbing NH3 previously to the reduction of NO is emphasized